2015
DOI: 10.1007/s11882-015-0520-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Markers of Difficult-to-Treat Severe Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a chronic inflammatory disease of the upper airways of which two major phenotypes exist, CRS without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP). Some patients with CRS have suboptimal response to current guideline treatments. These patients remain severe and uncontrolled by treatment and have a poor quality of life. It is highly important to identify both clinical and biological markers, so-called biomarkers, in this subset of patients. The presence of nasal polyps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 105 publications
1
29
0
1
Order By: Relevance
“…[1][2][3][4] CRS is a multifactorial inflammatory disorder with heterogeneous clinical features, histopathology, and efficacy of medications. [5][6][7] Such a heterogeneous nature of the disease confounds the identification of etiologic factors in patients with CRS. Defects in the innate immune system were recently proposed as important contributors to the initiation and amplification of inflammation in patients with CRS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] CRS is a multifactorial inflammatory disorder with heterogeneous clinical features, histopathology, and efficacy of medications. [5][6][7] Such a heterogeneous nature of the disease confounds the identification of etiologic factors in patients with CRS. Defects in the innate immune system were recently proposed as important contributors to the initiation and amplification of inflammation in patients with CRS.…”
mentioning
confidence: 99%
“…Primary interest has centered on regulation of eosinophils in patients with CRS because eosinophilic inflammation is dominant in patients with severe refractory CRS. 6,7 Thus there is growing attention to understanding the mechanisms that promote and perpetuate eosinophilic inflammation in patients with CRS.…”
mentioning
confidence: 99%
“…Comorbid asthma is known to be associated with other negative outcomes in patients with CRS. Previous studies have found that patients with comorbid asthma are more likely have more severe CRS (25) or more difficult to treat CRS (26) . Another study found that AECRS may precede asthma exacerbations (12) which on their own are associated with significant, negative clinical outcomes including increased mortality, poor pulmonary function, increased healthcare expenses and decreased productivity (14,19) .…”
Section: Discussionmentioning
confidence: 97%
“… 5 However, many patients report relapsing symptoms and need several surgical polypectomies; therefore, severe CRSwNP is hardly controlled by common therapies. 19 Similarly, severe asthma often results to be uncontrolled despite the use of high dosages of inhaled corticosteroids (ICS) and long-acting β 2 -adrenergic (LABA) bronchodilators. 20 Hence, current GINA (Global Initiative for Asthma) guidelines recommend at step 5 the utilization of add-on biological drugs for severe asthma.…”
Section: Introductionmentioning
confidence: 99%